Association of the Toxigenic Dinoflagellate Alexandrium ostenfeldii With Spirolide Accumulation in Cultured Mussels (Mytilus galloprovincialis) From Northwest Mexico - Paredes-Banda, Patricia; García-Mendoza, Ernesto; Ponce-Rivas, Elizabeth; Blanco, Juan; Almazán-Becerril, Antonio; Galindo-Sánchez, Clara; Cembella, Allan (Frontiers in Marine Science, 2018)
Spirolides are polyether cyclic imines considered as “fast acting toxins”. Long term human health consequences of spirolide ingestion are uncertain, and hence regulatory limits for human consumption have not been established. Nevertheless, monitoring these toxins in shellfish is essential because they can interfere with detection by mouse bioassay of lipophilic regulated toxins. Todos Santos Bay (TSB), in the northeast of the Baja California Peninsula, is an important shellfish cultivation and fish-farming area in Mexico. The toxin analog 13-desmethyl spirolide C has been reported in cultivated mussels (Mytilus galloprovincialis) from TSB, but the causative species associated with accumulation of this toxin has not been previously identified. We assessed the occurrence of Alexandrium ostenfeldii, the unique known producer of spirolides, by inverted light microscopy and by PCR with species-specific oligonucleotides designed for the ITS and 18S rDNA. We determined the presence and abundance of this species at the surface and at the thermocline from samples collected over two annual sampling periods (2013 - 2014 and 2016 – 2017). During the 2013-2014 period, A. ostenfeldii was found in 50% of the samples analyzed by light microscopy. The highest cell abundance (about 3.6 x 103 cells L-1) occurred in October 2013. During 2016 – 2017 the dinoflagellate was present in low cell abundances (<5 x 102 cells L-1) and was detected in only 20.9% of the samples. Cells of this species were usually found when sea surface temperature ranged from 17 to 20 °C. We also evaluated spirolide accumulated in cultivated mussels from TSB by tandem mass spectrometry (LC-MS/MS). The only spirolide detected was 13-desmethyl spirolide C, found mainly during the 2013-2014 sampling period, with the highest concentration (1.05 μg kg-1) in June 2014. During winter, toxin concentration was at or below the detection limit. During 2016-2017, spirolides were below the detection limit, coinciding with the absence of the causative species. Cell abundance of A. ostenfeldii and spirolide concentration in mussels did not present a clear correlation. This study represents the first record of A. ostenfeldii in TSB and provides evidence that this species is the primary origin of spirolides accumulated in mussels.